Creative Design of Decorative Additions in Fashion Design - Faten Ali Hussien; Salah Abdulghani Hussien (Journal of Techniques)
The decorative additions were a distinctive part and a prominent place in fashion design, which produced variants in the context of the form of supplements, whose parts are associated with the design of the costume. The presence of decorative additions may be excessive and may be taken as a predominant form, depending on the creative level of the designer in relation to the physical composition of the addendum, its type, location and methods of showing it in the fashion design of women. "What is the role of decorative additions and their effectiveness in fashion design? Objective of the research: "Know the creative role of decorations additions by revealing the vocabulary of addition and modalities in the design of women's fashion for the fashion designer (Zuhair Murad). " The theoretical framework included: decorating in fashion design, adding decorating as a creative process.. The research followed the descriptive-analytical approach, and the sample of the research was chosen intentionally, represented at the level of show and methods of creative formation of decorative additions in fashion design. The research reached the most important results such as the applied structural designs within the structure of the costume, using the cuttings, the folds and the collars as an additive associated with the construction of the uniform, emerged as formative variables of the same cloth material. And the simplistic addition showed that decoration retain the base form of the uniform, while the other showed the existence of multiple and complex decorative materials, both showing the correlation of the shape of the content in the costume design.